2017
DOI: 10.1002/jssc.201600884
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of total steroidal saponins from the extracts ofTrillium tschonoskiiMaxim by macroporous resin and the simultaneous determination of eight steroidal saponins in the final product by HPLC

Abstract: An effective and simple method was established for the separation and enrichment of steroidal saponins from Trillium tschonoskii Maxim. The adsorption and desorption properties of seven macroporous resins were investigated. Among the tested resins, AB-8 resin showed the best adsorption and desorption capacities. The adsorption of steroidal saponins on AB-8 at 25°C was quite consistent with both the Freundlich isotherm model and the pseudo-second-order kinetics model. By optimizing the dynamic adsorption and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…As described in the introduction section, recently saponins have become a research hotspot due to their multiple and strong bioactivities, especially their cytotoxic activities on a series of tumor cell lines related to their chemical structure (Bouabdallah et al, 2015;Nath et al, 2016;Zhang et al, 2016;Zhou et al, 2017). However our result also confirmed that the n-butanolic extract (saponin fraction) exhibited the best inhibitory activity on both of the leishmania parasites tested (Table II).…”
Section: Table IIsupporting
confidence: 81%
“…As described in the introduction section, recently saponins have become a research hotspot due to their multiple and strong bioactivities, especially their cytotoxic activities on a series of tumor cell lines related to their chemical structure (Bouabdallah et al, 2015;Nath et al, 2016;Zhang et al, 2016;Zhou et al, 2017). However our result also confirmed that the n-butanolic extract (saponin fraction) exhibited the best inhibitory activity on both of the leishmania parasites tested (Table II).…”
Section: Table IIsupporting
confidence: 81%
“…The eluate was collected, and then lyophilized with freeze-dryer (Zhou et al. 2017). Finally, the contents of total steroidal saponins were assayed using a diosgenin as reference by UV spectrophotometry.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, several steroidal saponins have been isolated and purified from the plants belonging to this genus and, at present, novel metabolites/phytochemicals from Trillium ssp. are investigating using the latest technologies [ 30 , 31 , 32 , 33 , 34 ]. The secondary metabolites/phytochemicals of species belonging to the genus Trillium are reported in Table 2 .…”
Section: Phytochemicals Of the Genus Trilliummentioning
confidence: 99%